Decentralised laboratories in the German energy transition. Why local renewable energy initiatives must reinvent themselves. (15th December 2017) - Beermann, Jan; Tews, Kerstin
Abstract: This study addresses research demands for a more critical empirical assessment of the innovation capacity of the decentralised, sub-national level. In Germany, the extensive involvement and contributions of new locally-rooted renewable energy initiatives have been one of the most striking features of the country's energy transition process. This study analyses the enabling conditions, current challenges and future prospects of decentralised experimentation in the German energy system. It finds that whereas the national support scheme has for a long period protected decentralised deployment of renewable energies by locally-rooted actors in the energy field, recent reforms of the scheme now threaten their further participation in the energy market. The paper observes that decentralised initiatives not only struggle to adjust to the new framework conditions. They have also not yet sufficiently addressed the new governance challenges arising from the fact that renewable energies have reached a stage of systemic importance for the whole power system, which requires decentralised initiatives to make their own efforts compatible with overall energy system transition needs. The study concludes that in order to remain an important innovator in the German energy transition, decentralised initiatives have to prove their ability to provide solutions to the systemic challenges of the energy transition process, such as horizontal and vertical multi-level coordination and decentralised contributions to the security of supply. Highlights: Energy transitions need "laboratories of innovation". The decentralised level is an apt setting for experimentation with scalable solutions. Locally-rooted new actors destabilised lock-in mechanisms in the German power sector. German energy policy reforms threaten decentralised experimentation. German bottom-up initiatives must reinvent themselves to remain innovators.